Dilemma in global governance of marine plastic pollution and regulatory coordination: convention reconstruction via integrated international law - Luo, Biao; Cao, Xia; Sun, Kerun (Frontiers in Marine Science, 2025)
Global governance of marine plastic pollution is facing fragmented regulations and conflicting enforcement. Drawing on Art. 207 of the United Nations Convention on the Law of the Sea (UNCLOS), this study, by examining overlapping jurisdiction across 17 international instruments, including the London Dumping Convention, the International Convention for the Prevention of Pollution from Ships (MARPOL Convention), and the limited effectiveness of regional regimes such as the Convention for the Protection of the Marine Environment of the North-East Atlantic (OSPAR Convention),identifies a gap between “soft law priorities” and “hard law absence”, particularly regarding microplastic control. To address this, the paper proposes an integrated framework—an umbrella convention plus specialized protocols: vertically, aligning the Global Plastic Treaty (GPT) with the Paris Agreement’s carbon market mechanisms; horizontally, enhancing cross-border technology transfer and extended producer responsibility (EPR) through the Basel Convention amendments and mutual recognition of regional standards. Key GPT provisions include: 1) transforming the precautionary principle into a no-regression clause, setting global plastic production caps with regular reviews; and 2) clarifying the Marine Protected Area (MPA)-specific rules under the Marine Biodiversity of Areas Beyond National Jurisdiction (BBNJ Agreement) with enforceable thresholds and a “do no harm” clause. The study further advocates mandatory jurisdiction authorized to the International Tribunal for the Law of the Sea (ITLOS) under a multi-stakeholder governance model, following China’s “Blue Circle” pilots. All these options will hopefully help overcome land–sea governance fragmentation and lead to coherent global regulation of marine plastic pollution.